Favorable outcomes of hilar duct oriented hepatic resection for high grade Tsunoda type hepatolithiasis - Kim, Bong-Wan; Wang, Hee-Jung; Kim, Wook-Hwan; Kim, Myung-Wook (World journal of gastroenterology : WJG, 2006)
AIM： To evaluate the efficacy of hilar duct oriented hepatectomy for intractable hepatolithiasis, the ventral hilum exposure （VHE） method that has been applied by the authors. METHODS： From June 1994 to June 2004 for a period of 10 years, 153 patients who had Tsunoda type Ⅲ or Ⅳ hepatolithiasis, received hepatectomy at our institution. Among these patients, 128 who underwent hepatectomy by the VHE method were the subjects for the study. We analyzed the risk of this procedure, residual rate of intrahepatic stones, and stone recurrent rates. RESULTS： The average age was 54.2 years, and the male to female ratio was 1：1.7. The average follow-up period was 25.6 mo （6-114 too）. There was no postoperative severe complication or mortality after the operation. The rate of residual stones was 5.4% and the rate of recurrent stones was 4.2%. CONCLUSION： VHE is a safe surgical procedure and provides favorable treatment results of intractable hepatolithiasis. Especially, this procedure has advantage in that intra-hepatic bile duct stricture may be confirmed and corrected directly during surgery.